Continuous human presence without extensive reductions in forest cover over the past 2500 years in an aseasonal Amazonian rainforest. (14th March 2018) - Kelly, Thomas J.; Lawson, Ian T.; Roucoux, Katherine H.; Baker, Timothy R.; Honorio‐Coronado, Euridice N.; Jones, Timothy D.; Rivas Panduro, Santiago
ABSTRACT: The impact of pre‐Columbian indigenous communities on forest cover in Amazonia is highly contentious, particularly for the wettest forests. To contribute to this debate, we studied the vegetation and fire history of a site, Quistococha, which lies within the aseasonal forests of the northern Peruvian Amazon and is associated with independently dated pre‐Columbian and recent human occupation. Paired cores from swamp and lake environments were used to distinguish landscape‐scale changes in vegetation from local‐scale succession. An increased abundance of disturbance‐adapted taxa in the pollen record from the lake, but not swamp, since c . AD 1860 probably reflects extensive deforestation related to the expansion of the nearby city of Iquitos. However, previous persistent occupation of the site by pre‐Columbian indigenous communities, indicated by the charcoal record from the lake site, is not associated with evidence for similarly extensive disturbance of the landscape. The unique features of this site therefore demonstrate that occupation by indigenous communities over thousands of years was not associated with large‐scale deforestation. These results support an emerging model of persistent but localized impacts by pre‐Columbian indigenous communities on aseasonal Amazonian forests.